Issues and Challenges in Implementing Braden Scale to Assess Pressure Injury Risk: A Participatory Action Research in South-Eastern Indonesia - Buntoro, Ika Febianti; Datusanantyo, Robertus Arian; Koamesah, Sangguana M. J.; Wijaya, R. Pasifikus Christa; Handoyo, Nicholas Edwin (The Lingkar Studi Bedah Plastik Foundation and is affiliated with the Department of Plastic Surgery, Faculty of Medicine, Universitas Indonesia., 2025)
Background: Pressure injury (PI) is chronic wound over bony prominence that should be managed to avoid morbidity and increased costs. Braden scale (BS) has been used worldwide for almost forty years as PI's standard risk assessment tool. This study aimed to identify issues among nurses regarding the implementation of the PI risk assessment tool in a referral hospital in rural Indonesia.Methods: We performed two cycles of participatory action research (PAR) to initiate the BS implementation and to establish follow-ups accordingly in inpatient units. The PAR ensured the active roles of the 12 nurses and midwives who initially implemented the tool. The transcribed focused-group discussion (FGD) recordings were analysed following six steps of thematic analysis.Results: There were three main themes emerged. The themes were the nurses' understanding of the need for PI risk assessment, the increasing workload when implementing PI risk assessment, and the importance of the primary nurse role. The themes reflects the need for nurse practitioners to further implement the tool by seeking confirmation from the primary nurse's group. The ease and trialability of the BS enhanced the nurses' compliance with the new tool. The nurse manager and leader needed to concentrate on perceived innovation attributes to implement the PI risk assessment tool further.Conclusion: The PAR cycles have recruited early adopters and suggested implementing BS to assess PI risk. The role of hospital managers and leaders in ensuring continuity of implementation is crucial.